Tantangan Guru Dalam Implementasi Pembelajaran Berbasis Project Dalam Pembelajaran IPA di Sekolah Inclusive di Kota Tomohon Sulawesi Utara - Lay Kekek Marthina Marentek (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify challenges and teachers' readiness in implementing the Project-Based Learning model in Inclusive Schools. The research method used is descriptive qualitative research using open-ended and closed-ended questionnaires. Learning models that can be implemented in inclusive schools are varies since it needs to be adapted to the needs of students with special needs. One of example of learning model is the Project-Based Learning model. This model will improve students' abilities and skills in addressing real-world problems. The role of teachers in implementing the PjBL model is as a learning facilitator and monitors students' learning process. The results indicate that 70% of teachers still experience difficulties in planning, and  60% of teachers experience difficulties in implementing PjBL. However, 95% of teachers stated that the PjBL model can support the learning of students with special needs. The various challenges faced by teachers in implementing the PjBL model can be addressed through teachers training.